ChemInform Abstract: Hydrothermal Synthesis and Dehydration of CaTeO3(H2O): An Original Route to Generate New CaTeO3 Polymorphs. Issue 34 (August 2015) - Poupon, Morgane; Barrier, Nicolas; Petit, Sebastien; Clevers, Simon; Dupray, Valerie
Abstract CaTeO3(H2O) is prepared by microwave‐assisted hydrothermal reaction of Ca(NO3)2, TeO2, NaOH, and H2O (microwave furnace, autoclave, 185 °C, 1 h).